Group-Based Flipped Classroom as a Decolonial Pedagogy for Empowering Grade 11 Filipino Learners in Online Oral Communication - Ronald Quileste; Archie Daguimol; Christian Gem Blanela; Kenrich Gapasin; Amanie Hadji Ibrahim; Raya Discipulo; Jade Alfie Sale (Universitas Cokroaminoto Palopo, 2025)
In the 2025 Philippine postcolonial context, enduring colonial legacies in English L2 education intersect with digital inequities and socioeconomic marginalization, demanding decolonial pedagogies that foreground agency and collaboration. This critical case study examines the Group-Based Flipped Classroom (GBFC) as a decolonial approach to empower Grade 11 learners in online Oral Communication classes at Xavier University Senior High School. Employing mixed methods, it explores how GBFC promotes active listening, learner agency, and equity in virtual learning spaces. Data from pre/post-tests, dialogic interviews, observations, and reflective journals (n=48) revealed significant learning gains (Fair: 0.45–0.52 vs. Poor: 0.22 under teacher-centered methods). Qualitative insights highlight enhanced engagement and inclusivity, especially among low-SES and basic L2 learners, despite persistent connectivity challenges. Grounded in the Filipino ethos of bayanihan, GBFC challenges colonial hierarchies in English pedagogy and demonstrates potential for culturally responsive, equitable online education. Recommendations include technological support, teacher training, and wider implementation across schools.